Underutilized Lignocellulosic Waste as Sources of Feedstock for Biofuel Production in Developing Countries - Adewale Adewuyi (Frontiers in Energy Research, 2022)
The need for a reliable and sustainable energy source, stability in energy price and solution to environmental challenges of fossil fuel has led to searching for an alternative energy source to fossil fuel. Several alternative sources have been developed over time, but they are limited in one form or another. However, biofuel such as bioethanol has been identified as a superb alternative with superior properties to fossil fuel. One major challenge with biofuel is the high production cost resulting from feedstock, which may also serve as a food source. In order to address this challenge, research is focused on searching for cheap and sustainable feedstock for biofuel production. Currently, attention is on lignocellulosic waste as feedstock with a keen interest in developing the most appropriate technique for processing it to bioethanol, especially in developing countries, which is the focus of this review. This review involves converting lignocellulosic waste to bioethanol and the pretreatment steps involved as well as its challenges, prospect and economic aspect. Among the pretreatment steps reported, biological treatment remains outstanding but with a few challenges which can be managed. Biofuel has come to stay in developing countries with lots of opportunities that favours its production cost. Although the high cost of enzyme production has been identified as a challenge to the economic viability of lignocellulosic bioethanol, there is hope that developing an efficient bio-system for simultaneous saccharification and fermentation (SSF) and consolidated biomass processing may help circumvent the challenge. In conclusion, the effective utilization of lignocellulosic waste in an efficient biocatalyst system can serve as an economically viable means to overcome the challenge posed by fossil fuel.